Nursing research: A marriage of theoretical influences - Kari Toverud Jensen (Wiley, 2019)
Abstract Aim The aim is to examine PhD theses in nursing science, their purpose or aim and the theoretical approaches and methods employed. The study seeks to examine how such theses may be categorized, what they study, what theoretical approaches they employ and, in particular, to what degree nursing theory is employed as a current theoretical approach. Design This study has a descriptive qualitative design. Method This study complied with the Standard for Reporting Qualitative Research (SRQR). Data were collected from 61 PhD theses in nursing science published from 1994-2015, at University of Edinburgh. Results Twenty of the PhD theses used theoretical approaches with a sociological perspective and 12 used a psychological perspective. Eighteen of the PhD theses were based on theoretical approaches from philosophy, ethics, pedagogy, medicine or biology as a primary perspective. Nursing theories, in their conventional definition, have a limited presence in the theses examined.